A Fuzzy Cognitive Mapping Approach to Conduct Deficiency Investigation under SIRE 2.0 Inspection - Orhan, Muhittin; Celik, Metin (Transactions on Maritime Science, 2023)
Ship Inspection Report Programme (SIRE) 2.0 has recently become operational as a new vessel inspection regime in the tanker industry. This study proposes a methodology to analyse and address multiple deficiencies observed during SIRE 2.0 inspections. The methodology is structured based on Fuzzy Cognitive Mapping (FCM) to identify and analyse the causes of deficiencies derived from the International Maritime Organization (IMO) classification scheme, including the factors under key dimensions, such as diminished human performance, marine environment, safety administration, and management. An illustrative case study on a set of deficiencies has been conducted to ascertain the utility of the methodology. The results specifically reveal that inadequate situational communication and awareness, inadequate knowledge of ship procedures, regulations, and standards, inadequate supervision, being unaware of role or task responsibility, poor maintenance, etc. are the potential causes that might lead to the occurrence of deficiency items. Considering the dimension-based distributions of causes, the study highlights integrated preventive action recommendations specific to the analysed deficiency cases. Consequently, the study might help tanker shipping companies manage key challenges with SIRE 2.0 implementations.